Metaheuristic Techniques Based Detection of Faults in a Photovoltaic System Under Partial Shading Condition – A Review - P., Maruthupandi; G.D., Vikram (Recent Research Reviews Journal, 2025)
The growing demand for renewable energy has led to increased adoption of photovoltaic (PV) systems. However, their efficiency and reliability are significantly affected by partial shading conditions (PSCs), which cause power losses and fault occurrences. Traditional fault detection methods often fail to provide accurate and timely identification of shading-induced issues. To address this challenge, metaheuristic techniques have emerged as effective solutions due to their optimization capabilities in complex, nonlinear environments. This review explores various metaheuristic-based fault detection methods for PV systems under PSCs, analysing their effectiveness, advantages, and limitations. Key algorithms such as Genetic Algorithm (GA), Particle Swarm Optimization (PSO), Differential Evolution (DE), Ant Colony Optimization (ACO), and Artificial Bee Colony (ABC) are discussed, emphasizing their roles in improving fault detection accuracy. Additionally, hybrid approaches integrating machine learning and metaheuristic algorithms are reviewed to assess their potential in enhancing fault diagnosis. The study aims to provide insights into the most efficient metaheuristic techniques for fault detection, emphasizing their application in real-time PV system monitoring. Future research directions and challenges in implementing these techniques are also outlined to facilitate further advancements in PV fault detection methodologies.